Angiogenesis in malignant melanoma. (February 2015) - Felcht, Moritz; Thomas, Markus
Summary Despite the development of novel therapies, the therapy of malignant melanoma remains challenging. Various studies have shown the vascular system to be pivotal for metastasis in melanoma. Consequently, the effect of various antiangiogenic therapies has been and is being investigated in preclinical and clinical trials. While most studies focus on inhibition of vascular endothelial growth factor (VEGF) signaling, others are aimed at determining the effect of multikinase inhibitors or the inhibition of angiogenic integrin activity. However, overall survival rates have not significantly improved in clinical trials with antiangiogenic agents. Resistance to anti‐VEGF monotherapy has been observed in several studies, especially in malignant melanoma. Angiopoietin‐2 (Ang‐2) represents a promising candidate molecule for antiangiogenic therapy and the effect of Ang‐2 inhibitors is currently being explored in first trials. In melanoma, Ang‐2 has been shown to be a marker for metastasis formation and represents an interesting therapeutic target molecule. Future studies are required to analyze the effect of a combined approach, using anti‐VEGF and anti‐Ang‐2, as therapy for malignant melanoma.